Archaeo-Tourism and Heritage Management A Case Study of Taxila Valley - Khan, Owais; Zahoor, Muhammad; Arif, Anus Mehmood Arif (University of Wah Journal of Social Sciences, 2022)
Taxila is the most famous World Heritage site in Pakistan. It is facing different problems from its executive departments as well as there are issues of tourists visits in the adjoining areas of Taxila. It is crucial to analyze the current situation and solve the problems at the management level and save “World Heritage Site.” New strategies are designed to regulate further, the data and the implementation plans. The findings of present research are based on effective management plans for the development of heritage sites. The study has given guidelines to the department of heritage and tourism as how to manage tourism effectively to decrease the damage done to these sites after the tourists’ visits. The tourists from Pakistan and abroad mostly pay a visit to cultural heritage sites of Taxila, as a result, the places suffer from irrecoverable damages.